PENGARUH KEBERADAAN PT. HUTAN KETAPANG INDUSTRI TERHADAP PENDAPATAN RUMAH TANGGA MASYARAKAT DI KECAMATAN KENDAWANGAN KABUPATEN KETAPANG (Jurnal Social Economic of Agriculture, 2017)
The method used in this research is quantitative research besifat. The research is descriptive quantitative research. Kuantiitatif descriptive study is essentially a research method or approach a case study (case study). This study focuses intensively on the object that is the effect of the existence of PT. Ketapang Forest Industry tehadap Household Income in Rural Communities Kedondong. The purpose of this study was to (a). Knowing the influence of the existence of PT. Ketapang Forest Industry on Household Income Communities in the District Kendawangan Ketapang. (B). Knowing how much influence the presence of PT. Ketapang Forest Industry on Household Income Communities in the District Kendawangan Ketapang. RESULTS: (1) .Hutan Industrial Plant PT. Ketapang Forest Industries give effect to the increase in revenue. Average Household Income Communities bigger than the Rural Household Income Kendawangan Right. That is evidenced by the average income of the respondents in the two areas of research that Kedondong village and the village of Kanan Kendawangan include major revenue, and revenue side of the family.